THE CIVIL LAW TERM 机关 JĪGUĀN IN TRANSLATION INTO ENGLISH, GERMAN AND POLISH - Joanna GRZYBEK (Comparative Legilinguistics, 2016)
The paper presents the options available when selecting equivalents of the Chinese term 机关  jīguān in legal context. The author undertook the conceptual analysis of the potential German and Polish equivalents of 机关 applied in the General Principles of the Civil Law of the People’s Republic of China of April 12, 1986  (中华人民共和国民法通则 Zhōnghuá Rénmín Gònghéguó mínfă tōngzé) and Civil Procedure Law of the People’s Republic of China of April 9, 1991  (中华人民共和国诉讼法 Zhōnghuá Rénmín Gònghéguó mínshì sùsòng fă). The corpus under study included the translation of the mentioned statutes into English proposed by Centre of Laws and Regulations in Law Press China (法规中心，法律出版社 Făguī zhōngxīn, Fălǜ chūbănshè). English and German are often intermediary languages in the process of finding equivalents in Polish-Chinese translation. The term 机关 used in a legal and/or administrative context is translated into English, German and Polish differently depending on the context.